2013
DOI: 10.1038/modpathol.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations are associated with solid growth pattern and tumor-infiltrating leukocytes in lung adenocarcinoma

Abstract: KRAS mutations define a clinically-distinct subgroup of lung adenocarcinoma patients, characterized by smoking history, resistance to EGFR-targeted therapies, and adverse prognosis. Whether KRAS- mutated lung adenocarcinomas also have distinct histopathologic features is not well established. We tested 180 resected lung adenocarcinomas for KRAS and EGFR mutations by high-sensitivity mass spectrometry-based genotyping (Sequenom) and PCR-based sizing assays. All tumors were assessed for the proportion of standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 52 publications
11
76
1
Order By: Relevance
“…For example, the metabolic region of EGFR1 tumors was smaller and had a lower SUV max than EGFR-tumors. Because of their low SUV uptake and smaller MTV, our results are consistent with the notion that EGFR mutants tend to be more indolent than other lung cancer types (39,40). In addition, 8 radiomic features were significantly associated with and predictive of EGFR mutation status, where InvDiffmomnor was the most predictive for EGFR mutation status and significantly outperformed the conventional measure MTV (P # 0.02).…”
Section: Discussionsupporting
confidence: 78%
“…For example, the metabolic region of EGFR1 tumors was smaller and had a lower SUV max than EGFR-tumors. Because of their low SUV uptake and smaller MTV, our results are consistent with the notion that EGFR mutants tend to be more indolent than other lung cancer types (39,40). In addition, 8 radiomic features were significantly associated with and predictive of EGFR mutation status, where InvDiffmomnor was the most predictive for EGFR mutation status and significantly outperformed the conventional measure MTV (P # 0.02).…”
Section: Discussionsupporting
confidence: 78%
“…However, KRAS mutations were less frequently indicated in the acinar predominant subtype (P=0.002) and adenocarcinomas with lepidic component (P=0.047), which was in consistent with the report by Rekhtman et al (29).…”
Section: A B C D E Fsupporting
confidence: 82%
“…Wang et al (26) did not identify any significant differences in histological subtypes between the KRAS mutations and the wild-types; whereas, Yoshizawa et al (14) and Kakegawa et al (28) indicated that KRAS mutations were significantly associated with adenocarcinoma of mucinous tumor subtypes (P<0.001). Rekhtman et al (29) showed that KRAS mutations occurred more often in adenocarcinomas with a solid growth pattern (P=0.022).…”
Section: A B C D E Fmentioning
confidence: 99%
“…14,15 Studies suggest that KRAS mutations are found in 17% to 37% of lung adenocarcinomas from white patients and 5% to 17% of lung adenocarcinomas from Asian patients. 13,[16][17][18][19] KRAS mutations are more frequently found in lung cancers from patients with heavy tobacco exposure, but they are also encountered among never-smokers with lung cancer. 20 Our study showed similar findings, with a 32% prevalence of KRAS mutation in our lung cancer series, including mutations in 83% of lung cancers from heavy smokers, but in only 8.5% of lung cancers from patients who were never-smokers.…”
Section: -13mentioning
confidence: 99%